“FAMILIAS E VEZINOS DEL COMERZIO”. THE MERCANTILE COMMUNITY IN LA VILLA DE ALBACETE, FORMS OF ECONOMIC ORGANIZATION AND SOCIAL REPRODUCTION AT THE END OF THE OLD REGIME - Gómez Carrasco, Cosme (Revista de Historia Social y de las Mentalidades, 2011)
At the end of the Old Regime in the town of Albacet e a social group connected to the commercial activities consolidated. A merchant community that was developed in tie to the agrarian activities. The position of this town in a crossroad between the capital of Spain and the Mediterranean periphery favored the economi c growth of these families. The objective of this essay is to understand its forms of economic organization and social 2 reproduction. The kinship was a key aspect in the e conomic management of the merchant businesses, but also in the social joint of these f amilies. The social bonds that united to these individuals were fundamental in their mobilit y and social reproduction. But also in the processes of changes and permanence at the end of the Old Regime.